Measuring Changes in Students’ Science Literacy through E-Module-Based Physics Learning Using Rasch Analysis - Abdurrohman Khotim Nugraha; Chaerul Rochman; Dindin Nasrudin; Fajriati Ramadhini Nur Mileniati; Siti Rahaimah Ali; Sitti Maesuri Patahuddin; Mosaddek Hossain; Dato Norsabrina Mohd Noor (Journal of Natural Science and Integration, 2026)
This study aims to measure changes in students' scientific literacy in physics learning through e-modules focused on momentum and impulse, using the stacking and racking Rasch model techniques. The study used a one-group pretest-posttest design involving 30 10th-grade students at a high school in Bandung. Data were analyzed using the stacking and racking Rasch model techniques to identify changes in students' scientific literacy and in item difficulty levels on the logit scale. Stacking analysis results showed that e-module-based learning could increase students' scientific literacy by 1.90 logits, while racking results indicated a decrease in item difficulty levels by -1.90 logits, suggesting that the improvement in scientific literacy directly affects how students respond to the measurement instruments. These findings indicate that integrating stacking and racking techniques provides a comprehensive view of the effectiveness of e-module-based physics learning, both in terms of changes in students' abilities and the functioning of test items. This study confirms that the Rasch model is a relevant approach for examining changes in science literacy in physics learning. Keywords: e-module, physics, Rasch model, scientific literacy, science education